Role of plankton communities in sea-air variations in pCO2 in the SW Atlantic Ocean - Schloss, Irene R. (2007)
The influence of the plankton community structure on carbon dynamics was studied in the surface waters of the Argentinean continental shelf (SW Atlantic Ocean) in summer and fall 2002, 2003 and 2004, The horizontal changes in plankton community respiration (R), net community production (NCP) and gross primary production (GPP) were (1) compared with the difference in the partial pressure of CO2 (pCO2) between the sea surface and the atmosphere (ΔpCO2), (2) compared with oxygen saturation and (3) related to the microscopic phytoplankton assemblages, This area, which has recently been shown to be a CO2 sink, had an average surface oxygen saturation of 108.1%, indicating that net photosynthesis could have played a dominant role in the CO2 dynamics. At most stations, the production:respiration (GPP:R) ratio was greater than 1, indicating that planktonic communities were autotrophic; the average GPP:R ratio for the whole study was 2.99, Phytoplankton biomass (chlorophyll a) and NCP showed an inverse relationship with ΔpCO2 and a direct relationship with %O 2 saturation when phytoplankton assemblages were dominated by diatoms (30% of the stations), This was not the case when small (≤5 μm) flagellates were the most abundant organisms, Although NCP was mostly positive for both groups of stations (i.e. diatom-dominated or small flagellate- dominated), other physical and biological processes are thought to modify the CO2 dynamics when small flagellates are the prevailing phytoplankton group.